2016
DOI: 10.1016/j.conb.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Target detection in insects: optical, neural and behavioral optimizations

Abstract: Motion vision provides important cues for many tasks. Flying insects, for example, may pursue small, fast moving targets for mating or feeding purposes, even when these are detected against self-generated optic flow. Since insects are small, with size-constrained eyes and brains, they have evolved to optimize their optical, neural and behavioral target visualization solutions. Indeed, even if evolutionarily distant insects display different pursuit strategies, target neuron physiology is strikingly similar. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Consistent with the CBA model, we found that when pursuing a bead moving at constant speed, the range vectors were close to being parallel across most of the trajectory: for 80% of the flight time, the absolute difference between each range vector and the trajectory median range vector was on average less than 3° (Figures 2A1–2A3; n = 63 attacks to a 1.3 mm bead). By applying proportional navigation, the guidance law associated with the CBA model [4, 7], a pursuer can control the necessary steering command to null any change in the velocity of the target, thereby keeping the range vectors parallel and actively maintaining the CBA (Figures S1G and S1H). We tested the CBA mechanism of Holcocephala by decelerating or reversing the bead during the attack (Movie S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the CBA model, we found that when pursuing a bead moving at constant speed, the range vectors were close to being parallel across most of the trajectory: for 80% of the flight time, the absolute difference between each range vector and the trajectory median range vector was on average less than 3° (Figures 2A1–2A3; n = 63 attacks to a 1.3 mm bead). By applying proportional navigation, the guidance law associated with the CBA model [4, 7], a pursuer can control the necessary steering command to null any change in the velocity of the target, thereby keeping the range vectors parallel and actively maintaining the CBA (Figures S1G and S1H). We tested the CBA mechanism of Holcocephala by decelerating or reversing the bead during the attack (Movie S1).…”
Section: Resultsmentioning
confidence: 99%
“…When this object is far away, we base the trajectory on the target’s location relative to an external frame of reference [1]. This process forms the basis for the constant bearing angle (CBA) model, a reactive strategy that ensures interception since the bearing angle, formed between the line joining pursuer and target (called the range vector) and an external reference line, is held constant [2, 3, 4]. The CBA model may be a fundamental and widespread strategy, as it is also known to explain the interception trajectories of bats and fish [5, 6].…”
mentioning
confidence: 99%
“…Vision plays an important role in insect behaviors, such as flight control (Srinivasan, ), prey detection (Gonzalez‐Bellido, Fabian, & Nordström, ), and collision avoidance (Simmons, Rind, & Santer, ). Large interneurons that respond to visual features relevant to these behaviors have been found in the third visual neuropil, lobula complex (LOX), in the optic lobe of the insect brain.…”
Section: Introductionmentioning
confidence: 99%
“…When dragonflies pursue and approach flying prey, they adopt a different tactic to tracking, called interception (Olberg, ; Gonzalez‐Bellido et al ., for review). When tracking, the pursuer aims directly at the perceived location of the target.…”
Section: Predatory Behavioursmentioning
confidence: 99%
“…Many use vision as the primary sense to detect prey (e.g. Gonzalez-Bellido et al, 2016) and some use cues from other modalities, including mechanoreception (e.g. Montgomery, 1982;Fertin & Casas, 2007) and chemoreception (e.g.…”
Section: Introductionmentioning
confidence: 99%